The Effect of the Ratio of Rice Flour and Breadfruit Starch (Artocarpus communis) on the Characteristics of Cendol - Listyana Dewi Farahdiga; Handayani, Catur Budi; Widyastuti, Retno (Journal of Food and Agricultural Product, 2024)
Breadfruit is a fruit that grows widely in Indonesia. The use of breadfruit is still very limited, namely fried or boiled as a snack. Breadfruit has a high carbohydrate content, resulting in quite a lot of starch extraction. One way to increase the use of breadfruit is to process it into breadfruit starch. Breadfruit starch has a high amylose and amylopectin content so it can be used as a chewing agent in cendol production. The aim of this research is to obtain the ratio of breadfruit starch in making cendol, by testing water content and total dissolved solids. The data obtained were analyzed using One Way Anova and to determine whether there were differences in treatment, it was continued with the Duncan Multiple Range Test (DMRT) with a significance level of 5%. The results of the research show that the correct ratio in making cendol to substitute breadfruit starch would be 25% rice flour and 75% breadfruit starch. The addition of breadfruit starch to making cendol has a significant effect on the water content of 81.37% -84.45%. The addition of breadfruit starch did not significantly differ from the total amount of dissolved solids with a value of 6.33-6.67 brix.